PEMBELAJARAN WIRAUSAHA DALAM MENDUKUNG PENGEMBANGAN EKONOMI PADA SISWA MADRASAH DINIYAH DARUL ULUM DI KABUPATEN PASURUAN - Wahyudi, *Setyo Tri; Badriyah, Nurul; Sari, Kartika; Nabella, Rihana Sofie; Radeetha, Radeetha (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2023)
The existence of gadgets for students can have a positive or negative impact. To minimize the negative impact of using gadgets, the service team carries out community service activities aimed at supporting economic development in elementary school students through entrepreneurial learning. Method of Implementation This service is carried out by delivering material related to entrepreneurship. To ensure that elementary school children understand entrepreneurship, groups were formed and asked to express their opinions and be active in discussions. Then, these elementary school students will be given rewards or gifts for those who are active in the discussion process. The results of the community service activities regarding entrepreneurial learning for elementary students were positively responded by teachers and students. With this service activity, elementary school students can increase their insight regarding entrepreneurship and can foster an entrepreneurial spirit at a young age. Moreover, the use of smartphones can be used as a means for entrepreneurship. Keberadaan gadget bagi para siswa dapat memberikan dampak positif maupun negatif. Untuk meminimalisir dampak negative dari penggunaan gadget, tim pengabdian melakukan kegitan pengabdian yang bertujuan untuk mendukung pengembangan ekonomi pada siswa Madrasah melalui pembelajaran wirausaha.  Metode Pelaksanaan Pengabdian ini dilakukan dengan cara penyampaian materi terkait kewirausahaan. Untuk memastikan anak-anak MADRASAH ini memahami terkait kewirausahaan maka dibentuk kelompok dan diminta untuk mengemukakan pendapatnya dan aktif dalam diskusi. Kemudian, siswa Madrasah ini akan diberikan reward atau hadiah bagi yang aktif dalam proses diskusi. Hasil dari kegiatan pengabdian mengenai pembelajaran wirausaha pada siswa Madrasah direspon positif oleh para guru dan siswa yang ditunjukkan dengan keaktifan mereka dalam proses pembelajaran wirausaha ini. Dengan adanya kegiatan pengabdian ini, siswa Madrasah dapat bertambah wawasannya terkait kewirausahaan dan dapat menumbuhkan jiwa wirausaha di usia muda. Terlebih, penggunaan smartphone dapat dimanfaatkan sebagai srana untuk berwirausaha.